Dimensionality and validity of the Gambling Motives Questionnaire – Financial among lottery loyalty program participants - Jihyeong Jeong; Paul Sacco (Addictive Behaviors Reports)
Objective: The Gambling Motives Questionnaire-Financial (GMQ-F) measures four gambling motives and these overlapping constructs may be distinct but also represent an overall gambling motivation. Thus, this study examined the scale’s factor structure by testing multiple-factor model configurations and then analyzing the association between these constructs and a problem gambling assessment. Methods: Data from a lottery loyalty program in a Midwestern state in the United States were analyzed (n = 6847). The dimensionality of the GMQ-F was tested using confirmatory factor analyses (CFAs) comparing three different models. A structural equation model (SEM) was used to assess the association between gambling motives using the best fitting model in the CFAs and problem gambling severity measured by the Problem Gambling Severity Index (PGSI). Results: Bifactor indices suggested limited multidimensionality with most of the variance explained by overall gambling motives, and limited variances explained by specific motives except financial motives. In the SEM, general motives were associated with a higher PGSI score. Social motives were associated with a lower PGSI score, while coping motives were associated with a higher score. Enhancement and financial motives showed no associations with PGSI scores. Conclusions: Our findings support the value of the GMQ-F as an instrument for measuring gambling motivation, with the caveat that the types of motivations or subscales are highly correlated. Future research should explore the financial gain as a distinct motivation for gambling.